Drug-Coated Balloon for Small Coronary Artery Disease in Patients With and Without High-Bleeding Risk in the BASKET-SMALL 2 Trial. (19th April 2022) - Scheller, Bruno; Rissanen, Tuomas T.; Farah, Ahmed; Ohlow, Marc-Alexander; Mangner, Norman; Wöhrle, Jochen; Möbius-Winkler, Sven; Weilenmann, Daniel; Leibundgut, Gregor; Cuculi, Florim; Gilgen, Nicole; Coslovsky, Michael; et al.
Abstract : Background: Patients at high-bleeding risk (HBR) undergoing percutaneous coronary intervention represent a challenging patient population. The use of drug-coated balloon (DCB) allows shorter duration of dual antiplatelet therapy compared with drug-eluting stents (DES) and reduces thrombotic risk due to the absence of a permanent implant. The present analysis aimed to investigate if the effect of DCB versus DES differed between patients with and without HBR treated with percutaneous coronary intervention in small coronary arteries. Methods: This prespecified subgroup analysis of a multicenter, randomized, noninferiority trial included 758 patients with de novo lesions in coronary vessels <3 mm and an indication for percutaneous coronary intervention, randomized to DCB (n=382) or second-generation DES (n=376). Patients were followed over 3 years for major adverse cardiac events. Results: Of the 758 patients randomized, 155 (20%) had HBR; these patients had higher mortality at 3 years (hazard ratio [95% CI], 3.09 [1.78–5.36]; P <0.001). Rates of major bleeding events were overall low but tended to be lower after DCB versus DES (1.6% versus 3.7%; P =0.064), were similar in patients with HBR (4.5% versus 3.4%) but less frequent in DCB-versus DES-treated patients without HBR (0.9% versus 3.8%). There was no difference in major adverse cardiac events between DCB and DES regardless of bleeding risk (HBR, hazard ratio: 1.16 [0.51–2.62]; P =0.719 versus non-HBR, 0.96 [0.62–1.49]; P =0.863). Conclusions: DCBs were similarly safe and effective as current-generation DES in the treatment of coronary arteries <3 mm, regardless of bleeding risk. In patients treated with DCB, there was a trend towards a reduction of severe bleeding events at 3 years. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01574534.